Validation of Dual Membrane Treatment for Indirect Potable Reuse - Linge, Kathryn; Blair, P.; Busetti, Francesco; Rodrigues, C.; Handyside, M.; Blythe, Justin; Bromley, M.; Lord, O.; Higginson, S.; Heitz, Anna; Joll, Cynthia; Newby, C.; et al. (Hallmark Editions, 2010)
The Western Australia's Premier's Collaborative Research Program (PCRP) project 'Characterising Treated Wastewater for Drinking Purposes Following Reverse Osmosis Treatment' commenced in October 2005, to determine the potential risks of replenishing drinking water aquifers with MF/RO treated secondary wastewater from Perth?s wastewater treatment plants. A brief report on the project won the Michael Flynn Award for the best poster paper at Ozwater 10. The results included those published in Water, February 2010, by Rodriguez et al, entitled Efficiency of RO for removal of Chemical Contaminants. Consequently, this version has been drafted to cover the other aspects of the study, principally the identification of suitable indicators which could be used to validate treatment performance.